СТИЛЕВЫЕ ОСОБЕННОСТИ ОПРЕДЕЛЕНИЙ В ФУНКЦИОНАЛЬНЫХ СТИЛЯХ УЗБЕКСКОГО ЛИТЕРАТУРНОГО ЯЗЫКА - Хужаниязов, Э. (SCIENCE and SOCIETY, 2019)
The article deals with the study of communitive role of attributes in speech. The author studies the functions and conditions of using attributes in defferent functional styles, their facultative and necessary forms.
Keywords: stylistic peculiarities; differentiation; scientific style; belles-litters style; facultative attributes; necessary attributes; functional style